Measurement of inclusive J/ψ pair production cross section in pp collisions at √s=13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kroesen, Martin; López, Jorge; et al. (Physical review, 2023)
The production cross section of inclusive J/ψ pairs in pp collisions at a center-of-mass energy √s=13 TeV is measured with ALICE. The measurement is performed for J/ψ in the rapidity interval 2.5<y<4.0 and for transverse momentum pT>0. The production cross section of inclusive J/ψ pairs is reported to be 10.3±2.3(stat.)±1.3(syst.) nb in this kinematic interval. The contribution from nonprompt J/ψ (i.e., originated from beauty-hadron decays) to the inclusive sample is evaluated. The effective double-parton scattering cross section is computed, neglecting the single-parton scattering contribution.
Veröffentlicht: 23. Oktober 2023
*ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, J. Crkovská, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, M. Kroesen, J.A. López, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. Van Veen, M.A. Völkl, B. Windelband, Y. Yuncu, F. Zanone [und 1017 weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 16.05.2024